Prednosti in slabosti bivanja ter potrebe lokalnih prebivalcev v Svečini, Turnišču in Cirkulanah - Žagavec, Aljaž (Revija za geografijo, 2023)
This study addresses the perceptions and needs of local residents in three rural areas. It compares the opinions of the residents with the strategic plans previously adopted by Local Action Groups and Regional Development Agencies. The results highlight the differences and similarities between the views of the local population and the strategic plans, prompting a discussion on the effectiveness and direction of regional development.
Keywords: Cirkulane; community needs; local perceptions; qualitative analyses; razvoj podeželja; regional policy; regionalna politika; regionalni razvoj; rural development; rural Slovenia; slovensko podeželje; strategic planning; strateško načrtovanje; Svečina; Turnišče